(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Computer network operations of organizations are always prone to cyber-attacks from different people, including misguided employees within the organization, due to the errors they make which lead to exploitation by cyber criminals. These people normally have destructive tendencies better known to themselves, as they would go to every extent to make sure that their nefarious intentions are achieved. It therefore, behooves on network operation technologists to innovate concrete and tested security measures to secure organizations’ network systems against hackers. The destruction could impact the activities of the organization to come to complete halt, as important information, a resource of the enterprise, may be damaged, stolen or lost. Some of these hackers may then turn around and demand huge sums of money from the organization before the stolen information may be released; likely the restored software may be tainted and therefore, different from the original state. Consequently, management of organizations should make adequate security preparations to forestall these destructive propensities of hackers. Vodafone Ghana therefore, should reinforce its security system to make sure the firewall and password systems, and access to its servers from the outside world are not compromised.